The Effect of Profitability, Sales Growth, and Capital Intensity on Tax Avoidance - Eka Prastiawati; Tumirin Tumirin (Universitas Muhammadiyah Gresik, 2022)
This study aims to analyze the effect of profitability, sales growth, and capital intensity on tax avoidance. This type of research is a quantitative research. In this study, researchers examined tax avoidance at consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the period 2018-2020 by using independent variables, namely, profitability, sales growth, and capital intensity The population of this study is the consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the period 2018-2020. The sampling method was purposive sampling and obtained as many as 94 samples. The data used in this study is secondary data in the form of financial statements of companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. The analysis technique used is multiple linear regression analysis, descriptive statistics, classical assumption test, and hypothesis testing with SPSS Version 25 program. The results show that profitability and sales growth have an effect on tax avoidance.